2013
DOI: 10.1177/1708538113504399
|View full text |Cite
|
Sign up to set email alerts
|

In situ revascularisation for femoropopliteal graft infection: ten years of experience with silver grafts

Abstract: Results of in situ implantation of silver-coated grafts for femoropopliteal prosthesis infection are according to our opinion acceptable, but the risk of reinfection remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…232,233 In a study of 24 femoropopliteal bypasses replaced with silver impregnated PET grafts, the overall re-infection rate was 19%. 234 When rifampicin soaked grafts are used, the results of wound cultures (when available) should be considered, as data have shown that the micro-organism causing the infection was resistant or not susceptible to rifampicin in 31% of cases. 235 A biosynthetic collagen prosthesis (Omniflow II; LeMaitre, Burlington, MA, USA) has also been tested in the presence of graft infection.…”
mentioning
confidence: 99%
“…232,233 In a study of 24 femoropopliteal bypasses replaced with silver impregnated PET grafts, the overall re-infection rate was 19%. 234 When rifampicin soaked grafts are used, the results of wound cultures (when available) should be considered, as data have shown that the micro-organism causing the infection was resistant or not susceptible to rifampicin in 31% of cases. 235 A biosynthetic collagen prosthesis (Omniflow II; LeMaitre, Burlington, MA, USA) has also been tested in the presence of graft infection.…”
mentioning
confidence: 99%
“…There are no wide studies on these materials, and, therefore, no definitive conclusions can be drawn. There is still little evidence for silver-coated grafts and bovine-pericardium xenogenous grafts, and further studies are needed to confirm their efficacy in VGEIs [16,22,[129][130][131][132][133][134][135][136]. Autologous femoral veins may also be used for an in situ reconstruction of the aorto-iliac segment in VGEIs [137][138][139][140].…”
Section: Treatment Of Vgeimentioning
confidence: 99%
“…However, they are definitely not the final solution for this serious and possibly lethal outcome complication [ 9 ]. The rate of re-infections of silver coated grafts in the femoral-popliteal segment is reported to be 19% [ 10 ]. Continuity of infection and bacterial resistance was found in 31% of patients after replacement of infected vascular graft with rifampicin coated prostheses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%